Peranan Vena Pulmonalis pada Fibrilasi Atrium - Dian Andina Munawar; Yoga Yuniadi (Jurnal Kardiologi Indonesia, 2012)
Background. Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia, occurring in1–2% of the general population and likely to increase in next 50 years. The prevalence of AF increases with age, from 0.5% at40–50 years, to 5–15% at 80 years. Precise mechanisms that lead tothe onset and persistence of AF have not completely been elucidated. The key role of ectopic foci in pulmonary veins as a trigger of AF has been recognized. Depending on disease progression, 60 to95% of triggers responsible for AF induction originate within the pulmonary veins (PV). Because of the clinical importance of the PVs in the initiation of AF, it makes the increasingly widespread application of catheter ablation techniques in these veins as a treatment for AF. Restoration and maintenance of sinus rhythm is of potential benefit if it can be achieved without the use of anti arrhythmic drugs, and this fact underscores the need to strive for the development of non pharmacological treatments to achieve and maintain sinus rhythm. Objective. The aim of the presentation is to discuss about role of pulmonary vein potential isolation on treatment of atrial fibrillation.Summary. A 64 year old man with diagnosis of paroxysmal atrial fibrillation was reported. The patient was then performed catheter ablation using CARTO 3D electroanatomic mapping system. He underwent pulmonary vein isolation and had successful result. In paroxysmal AF, PV electrical isolation remains a pivotal strategy. It is associated with arrhythmia suppression without the use of anti arrhythmic agents. The clinical outcome of ablation can further improved.